Larangan Perkawinan Karena Sepersusuan Perspektif Maslahah Mursalah - Pevi Yanti; Yufi Wiyos Rini Masykuroh; Uswatun Hasanah (Family Law Study Program, Faculty of Sharia and Law, UIN Sunan Gunung Djati Bandung, 2026)
This study aims to analyze the prohibition of milk-kinship marriage (rada‘ah) constitutes a fundamental provision in Islamic law aimed at preserving clarity in family relations and protecting lineage (nasab). However, in contemporary social practices, the understanding of the legal boundaries and implications of milk-kinship remains limited and is often neglected. This article analyzes the prohibition of milk-kinship marriage from the perspective of maslahah, emphasizing the urgency of lineage protection as an integral part of maqāṣid al-sharī‘ah. This study employs normative legal research using conceptual and normative-theological approaches by examining Qur’anic verses, Prophetic traditions, classical juristic opinions, and literature on maqāṣid al-sharī‘ah. The findings reveal that the prohibition of milk-kinship marriage functions not merely as a formal legal rule but also embodies preventive maslahah in safeguarding lineage, family stability, and social harmony. From the maslahah perspective, this provision remains highly relevant in preventing confusion in kinship structures and potential legal as well as social conflicts. This article affirms that the prohibition of milk-kinship marriage possesses strong rational and sociological justifications, ensuring its continued relevance in contemporary Muslim societies.